Analisis Perilaku Pengguna Terhadap Aplikasi Layanan Akademik STMIK Palangkaraya dengan Model UTAUT-3 - Kaestria, Rommi; Himmah, Elok Faiqotul (Jurnal Sains Komputer dan Teknologi Informasi, 2025)
The importance of information technology in higher education academic management encourages continuous evaluation of applications. The academic service application of STMIK Palangka Raya, SMART, which has been used since 2018 with e-learning and attendance features, needs to be evaluated for user acceptance for effectiveness and fulfillment of needs. This quantitative study aims to analyze the behavior of SMART users using the UTAUT-3 model. Data were collected through questionnaires from 291 users of the SMART STMIK Palangka Raya application and analyzed using Structural Equation Modelling (SEM) with the R application. The UTAUT-3 model in this study measures the influence of factors such as performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, habit, and price value on behavioral intention and actual use of the application. The results showed that facilitating conditions and price value had a significant positive effect on behavioral intention, while effort expectancy had a significant negative effect. Behavioral intention and habit had a significant positive effect on use behavior, while facilitating conditions and personal innovativeness had a significant negative effect on use behavior. This finding is crucial as a basis for increasing the adoption and utilization of academic information systems in a sustainable manner.